2016
DOI: 10.1038/nature18308
|View full text |Cite
|
Sign up to set email alerts
|

Translation readthrough mitigation

Abstract: A fraction of ribosomes engaged in translation will fail to terminate when reaching a stop codon, yielding nascent proteins inappropriately extended on their C-termini. Although such extended proteins can interfere with normal cellular processes, known mechanisms of translational surveillance are insufficient to protect cells from potential dominant consequences. Through a combination of transgenics and CRISPR/Cas9 gene editing in C. elegans, we demonstrate a consistent ability of cells to block accumulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 59 publications
5
101
1
Order By: Relevance
“…This limits the interaction between poly(A) binding protein and eRF3, leading to ribosomal pausing at PTCs, which makes them susceptible to readthrough (17). It was also recently found that cells can block the accumulation of proteins containing C-terminal extensions caused by translation past a normal termination codon and into the 3′-UTR by a mechanism that has not yet been elucidated (18). Thus, a combination of mechanisms prevent readthrough at normal termination codons.…”
Section: Discussionmentioning
confidence: 99%
“…This limits the interaction between poly(A) binding protein and eRF3, leading to ribosomal pausing at PTCs, which makes them susceptible to readthrough (17). It was also recently found that cells can block the accumulation of proteins containing C-terminal extensions caused by translation past a normal termination codon and into the 3′-UTR by a mechanism that has not yet been elucidated (18). Thus, a combination of mechanisms prevent readthrough at normal termination codons.…”
Section: Discussionmentioning
confidence: 99%
“…The finding is at odds with previous work 8 showing that proteins are generally destabilized when their sequences are extended by a stop-codon read-through. Yordanova and colleagues' experimental data collectively show that the effects of translation of the AMD1 tail ORF are independent of the main coding sequence, mRNA stability, common protein-degradation and cleavage pathways, or whether the expressed protein is secreted by cells.…”
Section: Limitless Translation Limits Translationcontrasting
confidence: 56%
“…7). But recent work 8 is helping us to understand that ECS values inferred from energy-budget changes over the past century are probably low, and shows that a higher value is more applicable when projecting future change. Applying such a correction to the original estimates 9 brings their values very much in line with Cox and co-workers' estimate ( Fig.…”
mentioning
confidence: 99%
“…Indeed, protein destabilization via readthrough extension has been reported earlier for the yeast PDE2 mRNA 21 and was recently proposed to be a general phenomenon 22 . To explore the effect of the extension on protein stability we designed additional constructs in which the AdoMetDC extension is fused to the C-terminus of GFP (Fig.…”
Section: Adometdc Catalyses the Decarboxylation Of S-adenosylmethionimentioning
confidence: 77%